PENERAPAN E–COMMERCE, KUALITAS PELAYANAN DAN KUALITAS PRODUK DALAM MENENTUKAN CUSTOMER RETENTION DI PIZZA HUT DELIVERY PADA KAWASAN KOTA DENPASAR - I Nyoman Jaya Artana; I Nengah Suardhika; I Gede Yudhi Hendrawan (EMAS, 2021)
The phenomenon of competition in the era of globalization will increasingly direct the country's economic system and market mechanisms, which in turn will position marketers to always develop in grabbing market share. In implementing good marketing, producers must know what the needs and desires of consumers are, so that the products offered will be in accordance with consumer demand.This study aims to determine and explain the application of e-commerce, service quality and product quality in determining customer retention at Pizza Hut Delivery in Denpasar City Area. The number of samples in this study was as many as 100 people. The sampling technique used was non-probability sampling with the accidental sampling approach. Data analyze technique with Structural Equation Modeling (SEM) to view the relation between the latent variable and the indicator (measurement model) and also to view the relation between a latent variable to another (structural model).The results of the analysis found that e-commerce variables and product quality have a positive effect in determining customer retention but service quality variables have no effect in determining customer retention at Pizza Hut Delivery in denpasar city area. This research is then expected to develop research using other variables that can theoretically influence in determining customer retention.